Rast in Nisbet-Hafen, nahe Makkovik (hier wurde 1752 der erste Missionsversuch gemacht) : [19--] - Lenz, Berthold, 1873-1960. (2001)
Black and white photograph of a group of missionaries having a picnic at Nisbet Harbour, near Makkovik. The caption indicates that this was where the first mission attempt was made in 1752. Black and white photograph of a group of missionaries having a picnic at Nisbet Harbour, near Makkovik. The caption indicates that this was where the first mission attempt was made in 1752.